The influence of competency and e-training to performance moderated by e-coaching within banking sales force - Nasra, Gita; Nugraha, Hindy Satya; Yuanita, Merina; Maharani, Anita (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
The purpose of this study is to analyze the relationship between competence and e-training on the performance of bank salespersons with e-coaching as a moderation. The literature referred to in this study is the concept of competence, e-training, e-coaching. The approach to this research is a quantitative approach, data collection is carried out by distributing surveys to Bank X's salespersons spread across 18 regional offices, from the results of the survey distribution 88 respondents were obtained. For the data analysis technique, this study uses the partial least square structural equality modeling approach. The results of the analysis show that e-coaching does not significantly moderate the effect of competence on performance or e-training on performance. In improving the competency in the form of hard skills in salespersons at Bank X, it can be done by holding workshops on presentation skills so that salespersons can convey product information effectively to customers. This skill is important to attract attention and convince potential customers. In addition, it also provides training on the latest sales techniques, including negotiation strategies and how to build strong relationships with customers. These skills will help salespersons improve their effectiveness in selling banking products.